Earthdivers. Volume three, 1776 - Jones, Stephen Graham, 1972- (Earthdivers, 2024)
"A team of time-traveling Indigenous survivors had one goal: save the world from an American apocalypse by sending one of their own on a suicide trip to kill Christopher Columbus and course-correct world history. Mission accomplished? Maybe not. Blood is still soaking into the sands of San Salvador as Tad's friends suffer the consequences of his actions--and their own slippery moral rationalizations--620 years in the future. Faced with a choice to watch the world crumble or double down on their cause, the path is clear for Seminole two-spirit Emily: it's personal now, and there's no better time and place to take another stab at America than Philadelphia, 1776. But where violence just failed them, she has a new plan: pass as a man, infiltrate the Founding Fathers, and use only wit and words to carve out a better future in the Declaration of Independence. No need to cut throats this time...right?"--